PROBLEMATIC REPRESENTATION AND CONSTRUCTION OF IDENTITY OF PAKISTANI WOMEN IN LAHORE WITH LOVE IN POSTCOLONIAL PERSPECTIVE - Umaimah Riaz Malik (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper examines Fawzia Afzal-Khan’s representation of Pakistani Muslim women in her memoir Lahore with Love: Growing Up with Girlfriends, Pakistani-Style. It critiques how Afzal-Khan constructs and represents the identities of Pakistani Muslim women, arguing that despite claiming to be a feminist, she often fails to respect the choices of other women. Instead, Afzal-Khan criticizes these women based on their religious beliefs, political views, and national contexts. Julia Kristeva’s theoretical perspectives on feminism, identity, and representation provide the primary analytical framework for this critique. Kristeva challenges traditional feminist frameworks that promote fixed, monolithic notions of ‘woman’ or ‘feminine,’ arguing that such views exclude the individuality of many women. She advocates for a politics of individuals rather than groups, emphasizing the importance of representing each person regardless of their sex, ethnicity, class, or other defining factors. Kristeva criticizes the imposition of rigid feminist ideals that demand conformity from women (such as not having children) as a prerequisite for their rights, viewing this as another form of repression replacing patriarchal norms. In light of Kristeva’s critique of fixed identities and homogenizing tendencies within feminist discourse, Afzal-Khan’s portrayal of Pakistani Muslim women is examined. The analysis highlights how Afzal-Khan’s representations may serve personal or ideological purposes, rather than genuinely reflecting the diverse identities and choices of these women. This paper draws on Kristeva’s ideas to question the authenticity and inclusivity of Afzal-Khan’s feminist stance, critiquing her approach as a form of misrepresentation that undermines the complexity of Pakistani Muslim women’s identities.